Kalibrasi dan Validasi Model Vissim untuk Mikrosimulasi Lalu Lintas pada Ruas Jalan Tol dengan Lajur Khusus Angkutan Umum (LKAU) - Jepriadi, Kornelius (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2022)
Currently, 2 (two) infrastructure projects are under construction on the Jakarta – Cikampek Toll Road, they are the Light Rail Transit (LRT) and the Jakarta – Bandung Fast Train. The construction of the project is indicated to be one of the causes of congestion on the road segment. The provision of bus lane (LKAU) on toll roads is one part of the policy package. LKAU which should be used by buses is actually widely used by non-bus vehicles, this certainly affects the performance of roads. To describe the changes in the performance of these roads, it can be measured by conducting traffic simulations. One of the software to perform microscopic simulation is Vissim. Where one of the processes that must be carried out in the software is calibration and validation. This research was conducted to obtain a calibration model that is able to describe the condition of the driver's behavior in the field. The calibration process is carried out by trial and error on parameters including Following Behavior, Lane change behavior, and Lateral behavior. The results showed that the parameter adjustment in the tailing (following), the settings were made by changing the CC0 (standstill distance) value from 1.5 m to 0.50 m, changing the CC1 (headway time) value from 0.9 to 0.5 seconds, changing the the value of CC2 (following variation) from 4 m to 7.5 m and changing observed vehicles movement,lateral namely changing the “desired position at free flow” from the middle of lane to any.